Randomized clinical trial of remote ischaemic preconditioning versus no preconditioning in the prevention of perioperative myocardial infarction during open surgery for ruptured abdominal aortic aneurysm. Issue 3 (26th March 2018) - Pedersen, T. F.; Budtz-Lilly, J.; Petersen, C. N.; Hyldgaard, J.; Schmidt, J.-O.; Kroijer, R.; Grønholdt, M.-L.; Eldrup, N.
Graphical Abstract: Abstract: Background: Remote ischaemic preconditioning (RIPC) has been suggested as a means of protecting vital organs from reperfusion injury during major vascular surgery. This study was designed to determine whether RIPC could reduce the incidence of perioperative myocardial infarction (MI) during open surgery for ruptured abdominal aortic aneurysm (AAA). Secondary aims were to see if RIPC could reduce 30-day mortality, multiple organ failure, acute intestinal ischaemia, acute kidney injury and ischaemic stroke. Methods: This randomized, non-blinded clinical trial was undertaken at three vascular surgery centres in Denmark. Patients who had open surgery for ruptured AAA were randomized to intervention with RIPC or control in a 1 : 1 ratio. Postoperative complications and deaths were registered, and ECG and blood samples were obtained daily during the hospital stay. Results: Of 200 patients randomized, 142 (72 RIPC, 70 controls) were included. There was no difference in rates of perioperative MI between the RIPC and control groups (36 versus 43 per cent respectively), or in rates of organ failure. However, in the per-protocol analysis 30-day mortality was significantly reduced in the RIPC group (odds ratio 0·46, 95 per cent c.i. 0·22 to 0·99; P = 0·048). Conclusion: RIPC did not reduce the incidence of perioperative MI in patients undergoing open surgery for ruptured AAA. Registration number: NCT00883363 (http://www.clinicaltrials.gov ).